Supporting the Concept of Genetic Predisposition to Prolonged Recovery Following a Concussion. Issue 7 (29th July 2014) - McDevitt, Jane; Tierney, Ryan; Phillips, Jacqueline; Gaughan, John; Torg, Joseph S.; Krynetskiy, Evgeny
Objectives: During a concussion, mechanical forces cause neuron cell strain that initiates dysfunction through the indiscriminate movement of ions through protein channels. Receptors of extracellular glutamate exacerbate the Ca2+ ion influx, and prolong neuron dysfunction. Genetic variations in the NMDA NR2A subunits (i.e., NR2A & NR2B) are likely to modulate the severity and/or recovery from concussion. Therefore, we hypothesized that genetic variability (e.g., repeat polymorphism) within the GRIN2A (i.e., gene that produces the NR2A subunit) promoter region was associated with concussion recovery time. Methods: Fifty-one athletes with a diagnosed concussion from a hospital concussion program completed a standardized initial evaluation. Concussion injury characteristics, acute signs and symptoms followed by an objective screening, which included the vestibular ocular assessments, the BESS test, and an ImPACT exam were assessed. Enrolled participants provided salivary samples for isolation of DNA. The number of (GT) variable nucleotide tandem repeats (VNTR) within the promoter region (i.e., region of the gene involved in transcription) of GRIN2A was genotyped. The long (L) allele was defined as an allele with ≥ 25 dinucleotide repeats in the GT tract. The short (S) allele was defined as an allele with < 25 dinucleotide repeats in the GT tract. Based on the results of genetic analysis, participants were genotyped as LL homozygotes, SS homozygotes, or LS heterozygotes. Participants' concussion recovery time was followed prospectively until the full return to play clearance date determined by the treating physician. Participant's recovery time was categorized as normal (≤ 20 days) or prolonged (greater than 20 days). The DNA region surrounding position (-975 to -776) in the promoter of GRIN2A was amplified by PCR, and was analyzed by capillary electrophoresis. Fragment length polymorphism analysis was performed by measuring the migration time of a PCR product, and extrapolation to the known fragments in the DNA standard ladder using computer software. The number of GT dinucleotide repeats was calculated using the following equation: n(GT)=(L - 167)/2, where L is the length of the PCR fragment estimated in base pairs. Results: There was a significant association (x2 = 4.01, p = 0.045) between the GT VNTR (recessive model: LL versus SS + LS) and recovery, where the chance of prolonged recovery was 4.3 times greater (95% CI1.03-18.04) for homozygous carriers of the long allele. Conclusion: This was the first study to investigate and demonstrate the association of the (GT)n VNTR within GRIN2A with concussion recovery in athletes. Athletes carrying the long allele genotype were predisposed to prolonged recovery following a concussive injury. We believe that genetic influence on concussion recovery will aid in future development of genetic counseling in athletes and individuals exposed to concussive head impacts. The clinical relevance of genotyping athletes could help improve monitoring and management of athletes who experience concussion injuries.